Organoids From Mucinous Appendiceal Adenocarcinomas as High-Fidelity Models for Individual Therapy - Liu, Guangyao; Xiao, Xing; Xia, Yujian; Huang, Weibing; Chen, Wei; Xu, Jiannan; Chen, Songyao; Wang, Huijin; Wei, Jitao; Li, Huan; Shu, Man; Lu, Xiaofang; et al. (Frontiers in Medicine, 2022)
Background: Mucinous appendiceal adenocarcinoma is a rare, heterogeneous disease. Patients with unresectable Mucinous appendiceal adenocarcinoma presenting with peritoneal spread are treated by intraperitoneal chemotherapy, hyperthermic intraperitoneal chemotherapy, systemic chemotherapy or targeted therapy. However, there are no guidelines for efficacious drugs against Mucinous appendiceal adenocarcinoma. Therefore, relevant high‑fidelity models should be investigated to identify effective drugs for individual therapy. Methods: Surgical tumor specimens were obtained from an Mucinous appendiceal adenocarcinoma patient. The tissue was cultured into organoids, after which the pathological characteristics, gene mutations and drug sensitivities of the organoid were compared to those of the original tumor. Results: Organoids were successfully established and stably passaged. Pathological characteristics of organoids as determined by HE staining and immunohistochemistry were consistent with those of the original tumor. Moreover, the organoids carried the same gene mutations as the primary tumor. Sensitivity of the organoids to chemotherapeutic drugs and tyrosine kinase inhibitors included: 5-FU (IC50 43.95 µM), Oxaliplatin (IC50 23.49 µM), SN38 (IC50 1.02µM), Apatinib (IC50 0.1 µM), Dasatinib (IC50 2.269 µM), Docetaxel (IC50 5.26 µM), Regorafenib (IC50 18.9 µM), and Everolimus (IC50 9.2 µM). These sensitivities were comparable to those of patients clinical responding to chemotherapy and targeted therapy. Conclusion: We have successfully established a Mucinous appendiceal adenocarcinoma organoid model which retained the characteristics of the primary tumor. Combined organoid-based drug screening and high throughput sequencing provides a promising way for Mucinous appendiceal adenocarcinoma treatment.